Characterization of the two-dimensional length and diameter distributions of gold nanorods by size exclusion chromatography - Lukas Hartmann; Nabi Traoré; Wolfgang Peukert; Johannes Walter (Scientific Reports)
Abstract Access to complex multidimensional property distributions of nanoparticle systems is indispensable for the understanding of their synthesis, processing and application in modern production technologies. Plasmonic gold nanorods are a system of particular interest due to their shape-dependent localized surface plasmon resonance. In this study, we show how the optical back coupling technique, previously developed for the analysis of sedimentation coefficient-resolved extinction spectra derived from analytical ultracentrifugation experiments, can be transferred to standard laboratory equipment, namely size exclusion chromatography. The optical back coupling method utilizes the unique spectral extinction of plasmonic nanoparticles such as gold nanorods and other geometries combined with their hydrodynamic properties to determine full size and shape distributions. Our technique opens up a simple and easy-to-use characterization platform that requires very little sample volume and provides multidimensional access to length, diameter, aspect ratio, volume and surface area distributions of plasmonic nanoparticles in one single experiment. We characterize a variety of gold nanorods of different aspect ratios and validate our results by complementary scanning transmission electron microscopy experiments. Finally, we provide an outlook on how this approach can be developed further.